2014
DOI: 10.1108/ijhcqa-05-2013-0053
|View full text |Cite
|
Sign up to set email alerts
|

Regulating healthcare complaints: a literature review

Abstract: The challenge of how to collect and harness complaints data to improve the quality of healthcare at a systemic level warrants further research. Scope also exists for researching health complaints commissions and other "meta-regulatory" bodies to explore how to make these processes fairer and better able to meet the complex needs of complainants, health professionals, health services and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
1
22
0
3
Order By: Relevance
“…A systematic review published in 2014 [34] highlighted the importance of strategic and responsive approaches to health complaints governance, including ‘ networked governance and flexible or responsive regulation ’, and the need to better understand how best to collect and harness complaints data to systematically improve service quality. The authors also argued for the need to examine the processes of complaints in health and social system contexts to make these processes fairer and better able to meet the complex needs of complainants, health professionals and society [34]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review published in 2014 [34] highlighted the importance of strategic and responsive approaches to health complaints governance, including ‘ networked governance and flexible or responsive regulation ’, and the need to better understand how best to collect and harness complaints data to systematically improve service quality. The authors also argued for the need to examine the processes of complaints in health and social system contexts to make these processes fairer and better able to meet the complex needs of complainants, health professionals and society [34]. …”
Section: Resultsmentioning
confidence: 99%
“…Issues of safety and quality of care account for 33.7% of all complaints, management-related issues (processes related to admission, discharge, billing, finances, referrals) for 35.1%, and problems in staff–patient relationships (behaviour, conduct, communication) for 29.1%. Another systematic review showed that in most parts of the world, complaint rates are low when compared to preventable adverse events; that certain groups use available complaint procedures more than others; and that people are more likely to complain informally than formally [34]. A review of 5,375 patient records from 14 hospitals in the Netherlands compared preventable adverse events with informal and formal patient complaints, medico-legal claims by patients and incident reports by staff [35].…”
Section: Introductionmentioning
confidence: 99%
“…Avhengighetsforhold mellom pasient-helsepersonell, sykdomsforløpenes dynamiske karakter og komplisert regelverk er viktige grunner til lav klagefrekvens i mange andre land (Beaupert et al, 2014), og trolig også i Norge. Manglende kjennskap til og forståelse av regelverket, må antas å vaere en viktig faktor når det gjelder manglende klagefrekvens.…”
Section: Diskusjonunclassified
“…Det er økende internasjonal interesse for å forske på klager i helsetjenestene (Beaupert et al, 2014). En litteraturstudie utgått fra et australsk forskningsmiljø viser at forskningen på dette feltet i all hovedsak har konsentrert seg om å kartlegge klagehyppigheten og hva man klager på, egenskaper ved klageren og utfallet av klager i ulike helsetjenestekontekster (Beaupert et al, 2014, s. 508).…”
Section: Diskusjonunclassified
“…[28] Communication as a precipitating factor in health care complaints clearly demands more attention. [29] Similarly, a 2012 report from the UK highlighted a 23 per cent increase in complaints against health professionals in relation to communication. [30] Communication skills are often a core competency required by registration bodies.…”
Section: Introductionmentioning
confidence: 99%